2008
DOI: 10.1111/j.1574-695x.2008.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometry as a tool for differentiation of invasive and noninvasiveStreptococcus pyogenesisolates

Abstract: A novel mass spectral fingerprinting and proteomics approach using MALDI-TOF MS was applied to detect and identify protein biomarkers of group A Streptococcus (GAS) strains. Streptococcus pyogenes ATCC 700294 genome strain was compared with eight GAS clinical isolates to explore the ability of MALDI-TOF MS to differentiate isolates. Reference strains of other bacterial species were also analyzed and compared with the GAS isolates. MALDI preparations were optimized by varying solvents, matrices, plating techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
42
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 43 publications
2
42
0
3
Order By: Relevance
“…The resulting protein spectra are postulated to be characteristic for each bacterial species. The available literature regarding the identification of and discrimination between subspecies or even single strains by MALDI-TOF MS is limited (1,24). Francisella tularensis subspecies were successfully discriminated with surface-enhanced laser desorption ionization-time of flight MS (SELDI-TOF MS) (19,26), a modified MALDI-TOF MS method which allows selective absorption of proteins on a chromatographic array surface prior to MS (31,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting protein spectra are postulated to be characteristic for each bacterial species. The available literature regarding the identification of and discrimination between subspecies or even single strains by MALDI-TOF MS is limited (1,24). Francisella tularensis subspecies were successfully discriminated with surface-enhanced laser desorption ionization-time of flight MS (SELDI-TOF MS) (19,26), a modified MALDI-TOF MS method which allows selective absorption of proteins on a chromatographic array surface prior to MS (31,32).…”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has been successfully applied to identify bacterial species (2,10,13,15,20,22,24,25) by measuring the mass of peptides and small proteins from whole cells. The resulting protein spectra are postulated to be characteristic for each bacterial species.…”
mentioning
confidence: 99%
“…By further improvement of the technique, a rapid, accurate, easy-to-use, and inexpensive method has become available for identification of microorganisms (4,14,27). MALDI-TOF MS can be used for accurate and rapid identification of various microorganisms, such as Gram-positive bacteria (2,3,9,10,22,26), Enterobacteriaceae (5), nonfermenting bacteria (6,(19)(20)(21), mycobacteria (12,16,24), anaerobes (10,23), and yeasts (18,25). Most studies have reported on MALDI-TOF MS identification of a single strain or family of microorganisms in a research setting.…”
mentioning
confidence: 99%
“…A study using an AB 4700 Proteomics Analyzer (Applied Biosystems, Foster City, USA) combined with the Tag-ident proteomics tool and the ExPASy sequence retrieval system (http://us.expasy.org) has shown that S. pyogenes isolates from necrotizing fasciitis clustered together and could be separated from noninvasive isolates, despite being the same emm types (5). However, the number of strains in the study was small (n ϭ 9) and, even using a larger collection, different emm types were not all separated by MS.…”
mentioning
confidence: 99%